The ethics of scientific research - T. Jacob T. Jacob (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1981)
Considering the importance of scientific ethics in research, especially if it involves human experimentation, the author discUsses various ethical points in conducting research from the preparation of research until the publication of its results. Emphases are placed upon responsibility CO the source of information, colleagues, research material, both human and animal, and humanity at large; scientific objectivity; and intellectual honesty.The need for research ethics cannot be overemphasized since deviation from the ethical principles are currently occurring even in the scientifically most advanced countries, due to, among others, the ''publish or perish" principle, pressure from funding agencies and research institutions, professional rivalries between individuals or institutions, and fights for priorities of discoveries and inventions.In the less developed countries the deviations are more elementary, but with the increasing quantity of research, complex problems are making their debut.Key Words: scientific ethics - human experimentation - informed consent - research review board - scientific objectivity